Effectiveness of Transcutaneous Electrical Nerve Stimulation Therapy on whole Salivary Flow in Patients with Xerostomia and Healthy Adults - Satish Chhugani; Gunjan Khatwani Chhugani; Abhishek Sahu Vishwa Pratap; Lokesh Adwani; Supreet Jain; Santosh Rayagouda Patil (Association of Support to Oral Health Research (APESB), 2021)
Objective: To evaluate and compare the effectiveness of transcutaneous electrical nerve stimulation (TENS) therapy on whole salivary flow in patients with xerostomia and healthy adults. Material and Methods:  Thirty subjects with a history of xerostomia and subjects with unstimulated salivary flow equal to or less than 0.5 ml in 5 min were included in the study group, and 30 healthy subjects were included in the control group. Low forced spitting unstimulated saliva was collected for five minutes in a test tube fitted with a funnel. Then electrode pads of the TENS unit were applied bilaterally on skin overlying the parotid glands and at optimal intensity, stimulated saliva was collected for 5 minutes with the same method in a separate graduated test tube. The salivary flow rate (per minute) was calculated by dividing the amount of collected saliva (volume in mL) by the duration of collection period (5 minutes) and the salivary flow rates prior and after electrostimulation were compared for both groups. The Student's t-test (unpaired and paired) was performed for group-wise comparisons. Results: In study group, the mean unstimulated salivary flow rate was 0.07 ± 0.01 mL/min. There was an 85.71% increase in salivary flow (0.13 ± 0.03 mL/min) during the TENS application and the difference was highly significant (p<0.001). In control group, the mean unstimulated salivary flow rate was 0.37 ± 0.07 mL/min. There was a 21.62% increase in salivary flow (0.45 ± 0.07 mL/min) during the TENS application and the difference was highly significant (p<0.001). An increase in mean salivary flow rate both in males and females after TENS application in both groups (p<0.001) was noted. The difference between unstimulated, stimulated and mean difference in salivary flow rate between males and females was not statistically significant in both groups (p>0.05). Conclusion: TENS can be an effective therapy in increasing whole salivary flow rates in patients with xerostomia.